Ultrasonic sensor detection system / Nor Khapiz Ismail - Ismail, Nor Khapiz (1999)
This paper describes the development of an ultrasonic sensor detection system. Since applications of an ultrasonic sensor system is very wide, this project focuses only on the security system. Ultrasonic sensor is normally used as an intelligent sensor, which used wave-propagation phenomena as a remote controller light. The development of ultrasonic transmitter and receiver operate at 23 kHz, above the hearing range of people. Ultrasomc waves can be detected and located for various material applications. The main device in this development is the transducer, which is designed for sending and receiving signal. The spectral and spatial radiation characteristic of transducer is the main determinant of sensor performance. The operating frequency in the range of 22 kHz to 26 kHz is a resonant that can produce the best output.